Sistem Pendukung Keputusan Penilaian Kinerja Guru Menggunakan Metode TOPSIS - Vieolita, Yoanda; Cici Ulandari (Journal of Decision Support System Research, 2024)
Teachers are one of the most owned components by the school in directing life, which is a challenge for the management of educational institutions to be able to provide an appropriate, effective and efficient decision in data management in the increasingly competitive business world spurring schools to work harder in improving the quality of their schools. So a decision support system is needed in determining the performance assessment of teachers in elementary or high school equivalent. And to determine who the teacher's performance at school requires criteria and weights in assessing it. To determine who is the teacher performance assessment, the Technique For Order Preference By Similarity To Ideal Solution (TOPSIS) method was used. This method was chosen because it is able to choose the best alternative from a number of existing alternatives. From a number of existing alternatives that become the best alternative for the best teacher performance assessment in elementary or high school equivalent.